Computer Application for the Evaluation of Mathematical Competence in Secondary Education: A Case Study - Orcos, Lara; Arias, Rosario; Magreñán, Á. Alberto; Sicilia, Juan Antonio; Sarría, Íñigo (Communications in Computer and Information Science, 2020)
The main purpose of this work is the development of an application that allows compulsory secondary education teachers the assessment of the students’ maths competence. An equation of prediction is obtained in a pilot study through the multivariate technique of multiple regression using for its analysis, by means of SPSS, the results gathered throughout speaking tasks, tests and works done by students in 2nd, 3rd and 4th course of compulsory Secondary Education of a state school in Spain. This equation of prediction is introduced in the program in order to make the calculation that provides the result of the assessment. The software is set up by means of interfaces. The source of information consists of a series of activities designed on the basis of liberated, national and international diagnostic tests taking into account the three key dimensions related to the maths competence: procedures, contents and context.
Ponencia de la conferencia "8th International Workshop on Learning Technology for Education Challenges, LTEC 2019; Zamora; Spain; 15 July 2019 through 18 July 2019"
Keywords: assessment; competences; computer application; diagnostic tests; maths competence; multiple regression; multivariate analysis; secondary education; Scopus(2); WOS(2)